Two different evolutionary lines of filamentous phages in Ralstonia solanacearum: their effects on bacterial virulence - Askora, Ahmed; Yamada, Takashi (Frontiers in Genetics, 2015)
The integration and excision of various filamentous phage genomes into and out of their host chromosomes occurs by site-specific recombination. The mechanisms proposed for these events include reactions mediated by phage-encoded recombinases and host recombination systems. Site-specific integration of filamentous phages plays a vital role in a variety of biological functions of the host, such as phase variation of certain pathogenic bacterial virulence factors. The importance of these filamentous phages in bacterial evolution is rapidly increasing with the discovery of new phages that are involved in pathogenicity. Studies of the diversity of two different filamentous phages infecting the phytopathogen Ralstonia solanacearum provide us with novel insights into the dynamics of phage genomes, biological roles of prophages, and the regulation and importance of phage–host interactions.